Concordance between maternal perception of weight and real weight of school childrens - Vega-Grimaldo, Miguel Angel (Universidad de Sonora, 2019)
Introduction: Overweight and obesity are associated to a greater extent for future complications in adulthood and to suffer chronic non-transmissible chronic diseases at an early age, an important factor that contributes to this is the inadequate perception that mothers have regarding their children´s weight. Objectives: To classify the maternal perception of their childrens weight by words and images in appropriate or inappropriate and the latter in underestimation or overestimation. Methods: Descriptiv transversal study, consisting of 30 dyads (mother child), sociodemographic data card was applied, survey to assess maternal perception by words/images and anthropometric measures were taken to the children. Information was analyzed through the SPSS statistical package, using descriptive statistics. Results: Greater adequate perception of the mothers was identified with respect of their children weight, by words and images (56.7% and 53.3%). In the inadequate perception, greater underestimation was identified in both perception by words and images (100% and 78.6%). Conclusions: There is agreement between the maternal perception of the weight and real weight of the schoolchild since there is a greater adequate perception between both variables. It is necessary to study other tools to raise awareness among mothers whose children have a weight problem.